The Role of Transformational Leadership in Enhancing EducationalQuality: Impacts on Teacher Motivation and Commitment - Rodiyah, Sinta; Puspitasari, Ria; Ar rauf, Ziddan; Diana, Nirva; Khabibjonovna, Kushieva Nodira (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
This study explores the role of transformational leadership in enhancing educational quality. As ongoing educational reforms call for improved learning outcomes, school leadership becomes a critical driver of meaningful change. The research examines how the four dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration contribute to teacher motivation, commitment, and professional growth. Using a systematic literature review that integrates national and international studies, the findings indicate that transformational leadership positively shapes teacher engagement and overall school climate. Idealized influence and inspirational motivation are particularly effective in fostering a supportive environment, whereas intellectual stimulation and individualized consideration show stronger effects when reinforced by adequate organizational structures and resources. The study concludes that effective school leadership requires not only the practice of transformational behaviors but also the cultivation of an organizational culture that promotes innovation and continuous professional development, highlighting the importance of proper training and resources for school leaders.